PROJECT ACTIVITY AS A TOOL FOR EUROPEAN INTEGRATION PROGRESS OF THE REGION - Вербовська, Леся; Запухляк, Іванна; Галюк , Ірина (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The purpose of this article is to analyze the preconditions for Ukraine’s European integration progress and its implementation of the Association Agreement as an effective tool for deepening trade and economic ties and improving the institutional environment for the implementation of reforms. As a result, the analysis was carried out in accordance with the methodology and methodology of the project, it was possible to effectively analyze the Index of European Integration Progress of Ivano-Frankivsk region for 2014 - 2020. The analysis showed that the region had significant fluctuations in terms of trade and economic activity and the European vector of development. The study on the indicator of the sub-index of trade and economic relations allowed to thoroughly analyze the export-import activity, analytical and consulting support of economic entities engaged in export-import activity. It is proved that the lack of a thorough analysis of foreign experience, based on the countries that have passed the preparatory stage of accession to the EU, showed the difficulty of business access to infrastructure and quality assessment of products prepared for export to EU countries. It is substantiated that the information policy of the region during the analyzed period was at a low level, the opportunities provided by the Association Agreement were not sufficiently covered for stakeholders. According to the results of the analysis, the sub-index of institutional support for Ivano-Frankivsk's European integration progress for 2014-2020 examined fluctuations due to: completion of the project phase of project implementation, reporting, monitoring, waiting for the announcement of the new competitive project period. and anticipation of project results. It is proved that in the pre-project period in the region measures were taken to write new project proposals, search for partners. It is substantiated that the focus on supporting European integration and cross-border cooperation are important tools in addressing pressing issues of regional development, as the intensification of these issues is identified as one of the priority areas of activity in Ukraine and the region.